The impact of migration on earnings of married men and women - Satu Nivalainen (European Regional Science Association (ERSA), 2001)
This paper examines differences in the outcomes of moving between married and unmarried individuals. Even if Amigration would be optimal for the family, it can be sub-optimal for one of the spouses. Unattached individuals instead, simply maximise their own personal welfare, and thus they should benefit from moving. In addition, there might exist gender differences in the outcomes of moving, especially in the family context. Therefore, both genders are investigated. The consequences of migration are examined both in terms of income and employment. A very large data set is utilised, and many-sided estimation techniques are used.
Keywords: 330